From COBOL to OOP - Knasmuller, Markus (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2004)
Driven by the year-2000 problem, the hordes of COBOL developers experienced a renaissance, but the times when COBOL was state-of-the-art are long gone. Object-orientation, application servers, web front-ends, and relational database systems dominate the scene for new projects today. The fact remains however, that millions of lines of source code written in the structured programming language COBOL work daily on computer systems all over the world. One problem that COBOL developers have to deal with on these new projects is familiarity with object-oriented concepts. Markus Knasmθuller, rich with experiences of OO projects in COBOL development teams, offers a successful introduction for the experienced COBOL programmer. A careful approach across techniques familiar to COBOL developers and discussions of current standards make this book easily accessible and understandable. *A practical approach to OOP using the concepts and techniques familiar to the experienced COBOL programmer. *Written independently from any specific programming environment, and all programming examples written in both Delphi and Java. *Detailed case study describing the successful migration of 10 million lines of COBOL code to object-oriented programming. *Companion CD-ROM containing all tutorial sections of the book in PowerPoint and all sample solutions to the problems ready for compilation.
Programming as an engineering discipline -- Basics -- Data structures and algorithms -- True object-oriented programming -- Object-oriented programming -- Databases -- Graphical user interfaces -- COBOL to OOP in practice.
Translation of: Von COBOL zu OOP.
Includes bibliographical reference (p. [329]-331) and index.
Keywords: Object-oriented programming (Computer Science).; COBOL (Computer program language); Electronic books